The Impact of Aid for Trade Facilitation on the Costs of Trading - Jens Königer; Matthias Busse; Ruth Hoekstra (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
There have been ongoing discussions within the WTO Doha Round on Trade Facilitation and the wider Aid for Trade agenda to assist developing countries in reducing behind-the-border restrictions and to help them benefit from trade reform. Our paper contributes to this debate by analyzing the impact of foreign aid spent on Aid for Trade and Trade Facilitation on the costs of trading. In our empirical investigation, we conduct a panel data estimation for a sample of 99 developing countries for the period 2004-2009. Overall, we find that our aid measures have a negative effect on the costs of trading.
Keywords: F13; F35; O19; 330; Trade Facilitation; Aid for Trade; Trade Costs